Twelfth rib syndrome: role of intercostal blocks: case series of 10 patients - Phadnis, Amit Prabhakar; Gadhe, Shashikant; Kale, Sachin; Vatkar, Arvind; Yadav, Praveen; Mandal, Shobhan; Verma, Ashmit; Das, Sonali; Kale, Sachiti Sachin (International Journal of Research in Orthopaedics, 2023)
Twelfth rib syndrome (TRS) is a rare condition that causes severe pain in the loin. It is often misdiagnosed, leading to unnecessary investigations and treatments. Intercostal blocks in the 11th and 12th rib often resolve the pain for these patients. In this research paper, we aim to explore the role of intercostal block in the management of TRS based on our experience with 10 patients. Data of patients who were diagnosed with TRS were studied retrospectively from our hospital records who have been given intercostal block injection from the period of Jan 2022 to August 2023 as an audit. Four patients underwent intercostal blocks. VAS scores were measured in follow-up for 1 and 3 months. 4 patients were lost to follow up and hence not considered in this study. The male to female ratio was 7:3. There was a statistically significant reduction in VAS score at 1 month and 3 months compared to pre-injection times. Patients who have failed conservative management for TRS can be effectively managed with intercostal block injections.